Al-Farabi and his treatises, which are based on practice - Kambarbekova, G.A. (Journal of Oriental Studies, 2020)
The article examines the life and little-known works of the famous scientist encyclopedist Abu Nasr Al-Farabi. A native of the Kazakh steppe, he is widely known for his deep knowledge and mastery of various disciplines. Abu Nasr Al-Farabi wrote treatises, articles and commentaries on various fields of science. According to the established tradition, Abu Nasr Al-Farabi is primarily a philosopher. He is also known for his individual treatises on all areas of the humanities. His treatises on mathematics and music have been translated into many languages of the world and are widely recognized. However, Al-Farabi’s works on medicine and chemistry are not widely known. For this reason, the article examines the small treatises of a famous scientist in the natural sciences and is considered from a modern point of view. Abu Nasr Al-Farabi’s works on natural sciences were translated into Russian on the eve of the 1100th anniversary of the scientist. Much time has passed since then, and these treatises have not received wide recognition. The article examines Al-Farabi’s work on medicine and chemistry in the light of current events. Every treatise by Al-Farabi is valuable, but his work on natural sciences allows us to get to know the scientist from a different angle. Key words: Al-Farabi, treatise, philosophy, logic, medicine, chemistry, anatomy, botanic, biology, natural sciences.